Hubungan Gaya Kepemimpinan Guru Mata Pelajaran IPS dengan Motivasi Belajar Siswa SMP Negeri 104 Jakarta Selatan - Cory Claudia; Gith Ciptaningtyas; Fadhilah Mujahidah (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2022)
The research aims to determine the relationship of social studies teacher’s leadership style with student’s learning motivation at SMP Negeri 104 Jakarta. The research uses a correlational method with a sampling technique obtained by 167 students from a population of 272 students. Data were analyzed with product moment correlation coefficient to test hypotheses and obtain conclution. The results showed that there was relationship between the leadership styles of social studies subject teachers in the classroom with students learning motivation, 1) the autocratic leadership style of social studies subject teachers in class was positively and significantly related to students learning motivastion as supporting leadership style, the results of the calculation of the correlation coefficient of 0.615 and the results of hypothesis testing with t-test obtained tcount (10,020) > ttable (1,974) with a significant level (?) = 0.05. 2) laissez faire leadership style of social studies subject teachers in class was positively and significantly related to students learning motivation as supporting leadership style, the results of the calculation of the correlation coefficient of 0.502 and the results of hypothesis testing with t-test obtained tcount (7.462) > ttable (1.974) with a significant level (?) = 0.05. 3) democratic leadership styles of social studies subject teachers in class was positively and significantly related to students learning motivation as dominant leadership styles, the results of the calculation of the correlation coefficient of 0.718 and the results of the hypothesis with the t-test obtained tcount (13.25) > ttable (1.974) with a significant level (?) = 0.05.